The Addition of Red Dragon Fruit and Lemon Peels for the Improvement of Fermented Beverage Products - Sofi Nabila; Arie Srihardyastutie; Sasangka Prasetyawan; Aulanni’am; Rurini Retnowati (Science and Technology Indonesia, 2023)
Coconut water is part of the coconut fruit, that has bioactive compounds that are thought to own high inhibitor activity to the presence of tannin compounds. However, this compound is antinutritional because it can interfere with macromolecule out there within the body. Considering chance of tannins, these parts are often reduced by fermentation techniques using lactic acid bacteria. This analysis aims to review the addition of dragon fruit and lemon peels in fermentation coconut water using lactic acid bacteria in order to reduce tannin levels and its potential capability as antioxidants. Coconut water fermented drink was prepared by fermentation technique using lactic acid bacteria with the addition of variations in mass of dragon fruit peel and lemon peel consisting of 5 treatments. The optimum conditions for fermentation of coconut water were determined from the decrease in tannin levels, total acid, and the highest total lactic acid bacteria. The optimum conditions for fermentation of coconut water were then tested using an HPLC instrument. Finally, the antioxidantactivity was tested using the FRAP (Ferric Reducing Antioxidant Power) method. The results showed that the addition of dragon fruit and lemon peels in fermented coconut water can reduce tannin levels, can increase total acid levels and the number of lactic acid bacteria formed in coconut water fermented drinks. The best proportion was obtained in the treatment of rasio of mass 1:2 resulted in the highest decrease in tannin content of 83.94 mg/100 g followed by a total acid value of 1.13% and the number of lactic acid bacteria was 8.4 × 107 CFU/mL. The HPLC chromatogram showed that fermented coconut water using lactic acid bacteria contained organic acid compounds such as lactic acid, acetic acid, and ascorbic acid. The highest antioxidant activity test was 82.37 mmgAAE/g. This study confirmed that the addition of dragon fruit and lemon peels affected the degradation of tannins and increased antioxidant activity during coconut water fermentation using lactic acid bacteria.